Enacting Project-Based Science - Marx, Ronald W.; Blumenfeld, Phyllis C.; Krajcik, Joseph S.; Soloway, Elliot (The Elementary School Journal, 1997)
Recommendations for reform in science education place a premium on students' understanding of scientific concepts and their ability to identify problems, conduct inquiry, and use information flexibly. They call for an appreciation for how ideas evolve and are validated. In this article we discuss changes in ideas about learning that underpin the reforms. We then describe our experiences with project-based science, a pedagogy that addresses the reform recommendations. Project-based science focuses on student-designed inquiry that is organized by investigations to answer driving questions, includes collaboration among learners and others, the use of new technology, and the creation of authentic artifacts that represent student understanding. Finally, we illustrate the challenges this type of innovation poses for teachers' classroom practice, for professional development, and for policy.
Keywords: enseignant